Pedestrian behaviour at unsignalised zebra crossing in university campus - Syahirah, Ibrahim (2019)
The interest toward promoting walking culture has been increased dramatically especially in many cities across the nation. This is also includes universities worldwide that have started seeking ways to increase pedestrian activities. Hence, campus planners must address the mobility and accessibility needs of pedestrian in their communities to ensure safety, functionality and conducive living and learning environment. However, there are several issues accounted in physical development planning that lead to failure in creating a conducive environment. Therefore, this study was conducted to evaluate the pedestrian preference, perception and behaviour towards the pedestrian facilities in university environment. In this scope of this study, the unsignalised zebra crossing in UMP Gambang and IIUM Kuantan was selected as study location. This study was conducted using qualitative and quantitative approaches by means of questionnaire distribution and also movement data collection. Then the Average Index Method was performed to indicate the pedestrian preference and perception towards the pedestrian facilities. In addition, the descriptive analysis of pedestrian behavior also has been analysed. Findings shows the students agree that using a pedestrian crosswalk save pedestrian time and more safety although during at night. Besides, IIUM student mostly not prefer to cross at designated pedestrian crosswalk compared with UMP students due to the locations not strategic and the numbers of crosswalk are not adequate. The mean speed of male pedestrian is significantly higher compared to female pedestrian in both universities. The waiting time for most pedestrian was very promptly as low as 2 seconds between both campuses. The mean walking speed of an individual is significantly higher compared to the group of three or more people between both campuses. By using statistical method of t-test, the significant two-tailed P value is less than 0.05. So, there is a statistically significant difference between UMP and IIUM in terms of speed distribution.